Evaluasi Aspek Konservasi Air berdasarkan Prinsip Green Building (Studi Kasus Gedung Griya Legita, Universitas Pertamina) - Dinanti, Hilsya Aliffia Putri; Qonitan, Fatimah Dinan; Ridhosari, Betanti (Journal of Sustainable Infrastructure, 2023)
Water conservation is an integral component of Green Building principles. Green buildings not only emphasize energy efficiency but also need to consider water resource conservation. Therefore, this research aims to conduct a study on water conservation in the campus environment of the University of Pertamina, specifically Griya Legita, with a focus on the implementation of Green Building principles. Through the analysis of water consumption, observation of existing water conservation efforts, and a comparison with the Greenship Existing Building version 1.1 Green Building standards, this study aims to identify potential improvements in water usage on the University of Pertamina campus. The research findings indicate that, based on the water conservation criteria in Greenship Existing Building version 1.1, a score of 9 out of a total of 20 points was obtained. Some of the implemented efforts include water monitoring control and freshwater efficiency. Areas for improvement include installing sub-metering for water consumption monitoring, conducting periodic laboratory testing of water quality, and enhancing management commitment and water conservation awareness among the campus community. The results of this study provide recommendations on how the campus can more effectively implement Green Building principles that involve water conservation.